Analisis Pengelolaan Formasi di Badan Kepegawaian Daerah Provinsi Kalimantan Tengah - Aprilia Aprilia; Nurul Hikmah (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
This research examines formation management at the Regional Staffing Agency of Central Kalimantan Province using a descriptive qualitative approach. The focus of the research includes the implementation of formation management, identification of the scope of routine activities, and development of optimization strategies. The results revealed that formation management has been implemented through various integrated aspects, including employee needs planning, formation preparation, staffing budget preparation, employee recruitment process, development and training, and performance evaluation. BKD Central Kalimantan Province has shown good performance in carrying out its duties and functions, focusing on developing employee competencies and increasing employee mobility as part of a quality formation strategy.